Successful Endoscopic Resection of Primary Rectal Mucosa-Associated Lymphoid Tissue Lymphoma by Endoscopic Submucosal Dissection: A Case Report - Han, Jian; Zhu, Zhe; Zhang, Chao; Xie, Hua-ping (Frontiers in Medicine, 2021)
Mucosa-associated lymphoid tissue (MALT) lymphoma arises in extra-nodal sites from the malignant transformation of B lymphocytes that are mainly triggered by infection or autoimmune process. MALT lymphoma is frequently detected in the gastrointestinal tract. As the causal relationship between Helicobacter pylori (H. pylori) infection and gastric MALT lymphoma, it was well-established that early-stage gastric MALT lymphoma could be cured by H. pylori eradication, and about 50–95% of cases achieved complete response with anti-H. pylori treatment. Compared to the stomach which is the most involved site due to the high prevalence of H. pylori infection, the colorectum is rarely affected. Primary rectal MALT lymphoma is a rare malignancy, and there are no specific therapeutic strategies so far. Here we report a case of rectal MALT lymphoma successfully resected by endoscopic submucosal dissection (ESD). ESD serves as a novel strategy to cure small localized rectal MALT lymphomas to avoid unnecessary surgery or chemo-radiotherapy.